2019
DOI: 10.1186/s12913-019-3991-7
|View full text |Cite
|
Sign up to set email alerts
|

Understanding performance data: health management information system data accuracy in Southern Nations Nationalities and People’s Region, Ethiopia

Abstract: BackgroundHealth management information system (HMIS) is a system whereby health data are recorded, stored, retrieved and processed to improve decision-making. HMIS data quality should be monitored routinely as production of high quality statistics depends on assessment of data quality and actions taken to improve it. Thus, this study assessed accuracy of the routine HMIS data.MethodsFacility based cross-sectional study was conducted in Southern Nations Nationalities and People’s region in 2017. Document revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
105
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(119 citation statements)
references
References 8 publications
6
105
2
Order By: Relevance
“…Yirgacheffe rural district had the highest deviation in terms of con rmed malaria records between HC and HO data followed by Dilla town and Dilla zuria district, whereas Wonago district was the least. Similar to our nding, a three-month facility-based study comprising of various settings conducted in southern Ethiopia showed that majority of facilities under-reported total malaria (both con rmed and clinical malaria) cases [10]. This in malaria data between the two systems, HC and HO, could be due to errors during entering the data from the sources (HCs) into recording formats of HMIS, lack of cross-checking and proo ng habits, training gaps on HMIS data use and unintentional/intentional false reports.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Yirgacheffe rural district had the highest deviation in terms of con rmed malaria records between HC and HO data followed by Dilla town and Dilla zuria district, whereas Wonago district was the least. Similar to our nding, a three-month facility-based study comprising of various settings conducted in southern Ethiopia showed that majority of facilities under-reported total malaria (both con rmed and clinical malaria) cases [10]. This in malaria data between the two systems, HC and HO, could be due to errors during entering the data from the sources (HCs) into recording formats of HMIS, lack of cross-checking and proo ng habits, training gaps on HMIS data use and unintentional/intentional false reports.…”
Section: Discussionsupporting
confidence: 89%
“…In Ethiopia, malaria data is captured through the health management information system (HMIS) at different tiers of the healthcare delivery systems. The hierarchy of data ow is from Health Posts (at kebele level) and Health Centers (HCs) to district health o ces (HOs) which in turn channels to Zonal Health Departments, then to Regional Health Bureaus and nally to the Federal Ministry of Health [10].…”
Section: Malaria Transmission In Ethiopia Is Seasonal Associated Withmentioning
confidence: 99%
“…Over-reported routine HMIS data is a challenge in many countries in SSA [24,28]. Our results indicate a clear reduction in the variation of the mismatch, especially for OPD and IPD service areas from 2014 to 2017.…”
Section: Discussionmentioning
confidence: 71%
“…Despite the increasing use of RHIS data for research purposes, the quality of these data remains imperfect and such issues should be identi ed and addressed in order to limit estimation error and bias. RHIS data quality issues remain a particular concern in some settings [113][114][115] , however, other studies have shown that strategies that have been implemented to improve RHIS data across different international contexts can be successful 5,116 . Multiple strategies were discussed in the articles we reviewed in our paper, including strategies to address common data quality issues such as missingness and data validity, for example the simple exclusion of missing data and various imputation and interpolation methods.…”
Section: Discussionmentioning
confidence: 99%